Thermal guidelines for data processing environments. (ASHRAE, 2012)
"This third edition of Thermal Guidelines for Data Processing Environments breaks new ground through the addition of new data center classes enabling near full-time use of free cooling techniques in the vast majority of the world's climates"-- Provided by publisher
Keywords: Data processing service centers -- Cooling.; Data processing service centers -- Heating and ventilation.; Buildings -- Environmental engineering.; Data processing service centers -- Design and construction.; Electronic data processing departments -- Equipment and supplies -- Protection.; Electronic apparatus and appliances -- Cooling.; elektronické knihy; electronic books